Everyday Agency: Rethinking Refugee Women’s Agency in Specific Cultural Contexts - Kanal, Maria; Rottmann, Susan B. (Frontiers in Psychology, 2021)
This article proposes an interdisciplinary approach to refugee agency - the capacity to act within structural conditions – using the example of Syrian women rebuilding family and home in Turkey. Our broader objective is to prompt a re-thinking of refugee women’s everyday agency for scholars researching migration. The dominant manner of studying agency tends to be centred on refugees’ efforts to change their particular situations. Drawing on the latest theoretical propositions of cultural psychology (collective coping and the cultural coping model), we argue that agency can also be observed through examining how refugees rebuild their lives in the face of the many changes and challenges they have experienced. Guided by the cultural coping model, we describe stressors and coping strategies in context. With this approach, we can escape the trap of viewing refugee women in dichotomous ways, either as traumatised victims or as liberated from “traditional patriarchy.” A total of 33 semi-structured interviews were conducted in Turkey with Syrian, Arabic-speaking adult women. Interviews aimed to obtain comprehensive narratives on acculturation, daily stressors, coping strategies and everyday experiences of uprootedness. We used constructivist grounded theory (Charmaz 2006) to identify significant themes (initial coding) and then code for more conceptual units of meaning (focused coding). The findings are structured around context specific themes: stressors and coping strategies. The study revealed three important types of stressors: family-related, role-related and place-related stressors. Each stressor can only be understood within the cultural context of inter-dependent agency, motherhood and neighbourhood belonging, which are highly valued lived experiences of the refugee women. The study also identified three coping strategies: faith-based, home-making and identity building strategies. Our research shows that relying on Islamic understandings, creating the routines of a happy home and forging neighbourly ties are important gender and culture specific manifestations of agency. The value of this research is that it provides migration scholars a useful model for designing research with female refugees. By identifying and writing about these specific and contextual forms of agency, researchers can provide better support to refugee women in their daily lives, while also challenging the image of passive “womenandchildren”.